TATA GUNA LAHAN DALAM TINJAUAN PENYUSUNAN KEBIJAKAN DAN PENGELOLAANNYA SECARA ISLAMI - Firmansyah, Aldrin Yusuf (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2010)
Land use is still one of the key elements of urban design. It determines the basic two dimensional plans on which three dimensional spaces are created and functions are performed. Urban is also a fusion of architecture, economics, history, geography, politics and religion. This entire aspects make a city has complex form. Islam as an amalgamation on community life, it contributes urban order include policy and management of land use. This paper has a purpose to explore Islamic contribution on arrangement of land use policy and management, from philosophical level to operational level. This paper uses methodical interpretative-historical research. It means investigations into social-physical phenomena that are a past condition, within complex contexts, with a view toward explaining those phenomena in narrative form and in a holistic fashion.Â